Efficacy of Acupuncture in Post-partum With Diastasis Recti Abdominis: A Randomized Controlled Clinical Trial Study Protocol - Liu, Yan; Zhu, Ying; Jiang, Liyuan; Lu, Chao; Xiao, Lijuan; Chen, Jiayu; Wang, Ting; Deng, Lujun; Zhang, Haida; Shi, Yingying; Zheng, Tingting; Feng, Min; et al. (Frontiers in Public Health, 2021)
Backgroud: Diastasis rectus abdominis (DRA) is one of the common complications during pregnancy and postpartum, which has both psychological and physical effects on postpartum women. Acupuncture, as a worldwide alternative therapy, which has attracted wide attention in the prevention and treatment of diseases related to pregnancy and childbirth. The purpose of this study is to evaluate the efficacy of acupuncture combined with physical training in the treatment of postpartum rectus muscle dissociation. Methods: This is a randomized, controlled trial of DRA in postpartum conducted at Guangxing Hospital Affiliated to Zhejiang University of Chinese Medicine. The primary purpose is to evaluate the effectiveness of acupuncture and physical training on DRA in postpartum women. The study will be conducted from March 2021 to March 2022. The acupuncture group received acupuncture and physical training (n=48), sham acupuncture group received sham acupuncture and physical training (n=48), and waiting-list group received physical training (n=48). These experiments perform once a day, which lasts 30 min to 60 min for each time.10 times of continuous treatment as a course of treatment, a total of one course of treatment, followed up for half a year after the end of the course of treatment. Our tests perform a course of treatment, which include a total of 10 consecutive treatments. Furthermore, the patient will be followed up for half a year after the treatment. Primary and secondary indicators, including inter recti distance (IRD), linea alba (LA) tension, the MOS item short form health survey (SF-36), short-form McGill pain questionnaire-2 (SF-MPQ-2), body mass index (BMI), waist-to-hip ratio (WHR), leeds dyspepsia questionnaire (LDQ), menstrual distress questionnaire (MDQ), 10 items of edinburgh postnatal depression scale (EPDS-10), the modified body self-image scale (MBIS), international consultation incontinence questionnaire short-form (ICIQ-SF) and hernia-related quality-of-life survey (HerQles), which will be evaluated before and after treatment and half a year after treatment. Adverse events and side effectivenesss during each treatment will be collected and recorded. Discussion: There is evidence that acupuncture and physical training can treat DRA in postpartum. In this study, we evaluate the effectiveness of acupuncture in postpartum with DRA. Clinical Trial Registration: ChiCTR2100046959.